(untitled) - The World Bank (WB) (Ha Noi, 2008)
Because of high mortality rates, high rates of contagion, and the possibility of cross-species infection to mammals including humans, high pathogenic avian influenza is a major concern both to consumers and producers of poultry. The implications of the avian influenza for international poultry markets are large and include the loss of consumer confidence, loss of competitiveness, loss of market shares, supply shortages, and disruptions of trade flows. This paper illustrates the effect that high pathogenic avian influenza has had on the trade flows of poultry products. The findings suggest that outbreaks of avian influenza have greatly restructured the international flow of poultry products. Consequent to high pathogenic avian influenze, Brazil has emerged as the world's largest supplier of frozen raw chicken products, while poultry industries in Southeast Asia have largely refocused their export markets by converting production from unprepared to prepared poultry meat.
Keywords: Birds as carriers of disease,Avian influenza,Chim làm vật chủ lây truyền bệnh,Cúm gia cầm